PERAN KECERDASAN EMOSI TERHADAP KEPEMIMPINAN OTENTIK PADA ORGANISASI KEPEMUDAAN - Muhammad Reiza (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
Leadership clearly has an impact on organizational success, and previous research has revealed the antecedents and consequences of the effects of leadership style and leader personality traits. The researcher's focus on the context of authentic leadership in youth organizations has received little attention and very little research on it, so the question arises: does the role of emotional intelligence affect authentic leadership practices in youth organizations. The researcher also observed from the side of emotional intelligence that affects authentic leadership, resulting in effective decision making in youth organizations. There are several problems faced by all leaders of youth organizations because of the various roles, attitudes, behaviors and emotions that affect leadership in managing the organization. This study uses a quantitative approach technique by distributing online scale questionnaires to 215 members of one of the youth organizations in Indonesia. Hypothesis testing was carried out using the multiple regression analysis method. The results of the analysis showed that emotional intelligence has a role in authentic leadership with an effective contribution of 58.4%.